2007
DOI: 10.1038/nature06098
|View full text |Cite
|
Sign up to set email alerts
|

Glucose sensing by POMC neurons regulates glucose homeostasis and is impaired in obesity

Abstract: A subset of neurons in the brain, known as 'glucose-excited' neurons, depolarize and increase their firing rate in response to increases in extracellular glucose. Similar to insulin secretion by pancreatic beta-cells, glucose excitation of neurons is driven by ATP-mediated closure of ATP-sensitive potassium (K(ATP)) channels. Although beta-cell-like glucose sensing in neurons is well established, its physiological relevance and contribution to disease states such as type 2 diabetes remain unknown. To address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
542
4
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 624 publications
(591 citation statements)
references
References 30 publications
18
542
4
7
Order By: Relevance
“…For instance, a recent study reported that transgenic expression in POMC neurons of a constitutively active Kir6.2 subunit, which generates K ATP channels that can no longer be regulated by glucose, led to complete unresponsiveness of these neurons to elevations in extracellular glucose concentration. 89 The feeding behavior of these mice was however normal, suggesting that glucose sensing by these cells was not critical for the physiological control of feeding. The metabolic sensor AMP-activated kinase, which is activated by low glucose concentrations, may also participate in the control by glucose of feeding through a regulation of the melanocortin pathway.…”
Section: Feeding Controlmentioning
confidence: 92%
“…For instance, a recent study reported that transgenic expression in POMC neurons of a constitutively active Kir6.2 subunit, which generates K ATP channels that can no longer be regulated by glucose, led to complete unresponsiveness of these neurons to elevations in extracellular glucose concentration. 89 The feeding behavior of these mice was however normal, suggesting that glucose sensing by these cells was not critical for the physiological control of feeding. The metabolic sensor AMP-activated kinase, which is activated by low glucose concentrations, may also participate in the control by glucose of feeding through a regulation of the melanocortin pathway.…”
Section: Feeding Controlmentioning
confidence: 92%
“…In addition, peripheral hyperglycemia in rats increased hypothalamic glucose levels and suppressed EGP, whereas inhibiting central metabolism of lactate partially abolished suppression of EGP by hyperglycemia (16). Further studies showed that transgenic mice with impaired glucose sensing by pro-opiomelanocortin (POMC) neurons due to expression of a mutant Kir6.2 subunit developed impaired glucose tolerance (18). Additionally, obese mice on a high fat diet developed similarly impaired firing of POMC neurons in response to glucose (19).…”
Section: Evidence For Cns Nutrient and Hormone Sensing In Animalsmentioning
confidence: 99%
“…The original Ucp2 −/− mouse, established on a mixed 129/SVJ × C57BL/6 background [11], exhibited increased glucose tolerance and increased GSIS. Part of this phenotype may have been caused by improved glucose responsiveness, as UCP2 is also involved in the response to glucose in pro-opiomelanocortin (POMC) neurons [25], but the main mechanism behind the improved glucose tolerance phenotype in these UCP2-deficient mice was proposed to occur in the β-cells. In contrast, when this global Ucp2 −/− strain was recently backcrossed onto three different genetic backgrounds, GSIS was not stimulated [26].…”
Section: Uncoupling Proteins and Gsis In Micementioning
confidence: 99%